Perbandingan Pembelajaran Kooperatif Talking Chips Dengan Konvensional Dan Keaktifan Siswa Terhadap Hasil Belajar Ekonomi SMA N 1 Kecamatan Guguak Lima Puluh Kota - Sri Gustina Dinova; Syamwil Syamwil (Universitas Negeri Padang, 2023)
The purpose of this study is 1) To compare student learning outcomes in economics subjects in class XI SMA N 1 Kecamatan Guguak Lima Puluh Kota using the talking chips cooperative learning model versus the conventional model, 2) To compare the learning outcomes of students who are more active in economics subjects with students who are less active in class XI SMA N 1 Kecamatan Guguak Lima Puluh Kota, 3) To investigate the interaction of the talking chip cooperative learning model and traditional learning with activity in class XI economics subjects at SMA N 1 Kecamatan Guguak Lima Puluh Kota. This is a quasi-experimental study. Purposive sampling is a technique used in sampling. Through